Resilient RFID Grouping Proofs with Missing Tag Identification - Burmester, Mike; Munilla-Fajardo, Jorge (Springer, 2016)
The adoption of RFID (Radio Frequency Identification) technology has greatly improved the efficiency of inventory control, supply-chain management and logistics. With RFID group scanning, an RFID reader scans a group of RFID tagged objects to generate a grouping proof of “simultaneous” presence. Shipments may have to be tracked remotely by readers that are not necessarily trusted. In this paper we extend earlier work on grouping proofs and group codes to capture resilient group scanning with untrusted readers. We present a two-pass anonymous grouping proof (of integrity) for the scanned objects of a (not necessarily complete) collection of RFID tagged objects that identifies missing objects. The proof is generated by an untrusted reader and can be checked by a verifier, a trusted entity. We only assume that RFID tags are able to generate pseudorandom numbers and compute one-way hash functions.
Keywords: Radiofrecuencia; Osciladores de radiofrecuencia; RFID; Resilient; Security; Supply chain; Grouping proofs